Interaction of Type 1 Porcine Reproductive and Respiratory Syndrome Virus With In Vitro Derived Conventional Dendritic Cells - Li, Yanli; Mateu, Enric (Frontiers in Immunology, 2021)
The present study delineates the interaction of a typical PRRSV1.1 isolate 3267 (moderate virulence) with in vitro derived pig conventional dendritic cells, cDC1, cDC2, and a CD14+ population (designated as CD14+ DCs). cDC1 and cDC2 were not susceptible to 3267 infection, but a fraction of CD14+ DCs were infected. After exposure to the virus, all three DC types remained immature as determined by no increase of maturation molecules (MHC-I, MHC-II, CD80/86, CCR7), no release of cytokines, no modification of antigen presentation abilities, and no alteration of endocytic/phagocytic capabilities. However, when infected MARC-145 cells were used as a source of viral antigens, cDC2 and CD14+ DCs showed a significant increase in the expression of maturation molecules and substantial release of cytokines, notably IL-12/IL-23p40 (by both DC types) and IL-10 (by CD14+ DCs). To address the impact of PRRSV1 3267 on TLR3- and TLR7-mediated activation, cDC1, cDC2, and CD14+ DCs were inoculated by the virus (live or UV-inactivated) for 6 h prior to or simultaneously with the addition of poly I:C (TLR3 ligand) or gardiquimod (TLR7 ligand; not used for cDC1). Compared with using TLR ligand alone, combination with the virus did not result in any alteration to the maturation markers on all DC types but changed the cytokine response to either TLR3 or TLR7 ligand. Pre-exposure of cDC2 or CD14+ DCs to the live virus resulted in an increased production of IFN-α upon poly I:C stimulation, while pre-exposure to UV-inactivated virus tended to enhance the release of IL-10 upon gardiquimod stimulation. Simultaneous addition of the live virus and the TLR ligand either had no effect (mainly in cDC2) or impaired most of the cytokine release after gardiquimod stimulation (in CD14+ DCs). When used as antigen presenting cells, cDC2 pre-inoculated by the live virus before addition of gardiquimod impaired the proliferation of CD4–CD8– T cells. In the case of CD14+ DCs, pre-exposure to the live virus or simultaneously added with TLR3 or TLR7 ligand largely decreased the proliferation of CD4–CD8+ and CD4–CD8+ T-cell subsets. For cDC1, no significant changes were observed in cytokine responses or T-cell proliferation after poly I:C stimulation. Of note, cDC1 had a short life during in vitro culturing, for which the results obtained might be biased. Overall, exposure to PRRSV1 did not induce maturation of cDC1, cDC2, or CD14+ DCs, but modified TLR3 and TLR7-associated responses (except for cDC1), which may affect the development of adaptive immunity during PRRSV1 infection. Moreover, the sensing of infected cells was different from that of the free virus.